The Treatment with Interleukin 17 Inhibitors and Immune-Mediated Inflammatory Diseases - Laura Țiburcă; Marius Bembea; Dana Carmen Zaha; Alexandru Daniel Jurca; Cosmin Mihai Vesa; Ioana Adela Rațiu; Claudia Maria Jurca (Current Issues in Molecular Biology, 2022)
IL-17 inhibitors (IL-17i) are medicines used to treat dermatological and rheumatic diseases They belong to a class of medicines called biological disease-modifying anti-rheumatic drugs (bDMARDs). This class of drugs has had a major impact on the therapy of autoimmune diseases, being much safer and more effective than treatment with small molecules. At the same time, they have highly beneficial effects on skin and joint changes, and their efficacy has been extensively monitored and demonstrated in numerous clinical trials. More and more such drugs are still being discovered today to ensure the best possible treatment of these patients, but more frequently and relatively constantly three agents are used. Two of them (Secukinumab and Ixekizumab) inhibit IL-17A directly, and the third, Brodamulab, inhibits the IL-17A receptor. Although they are extremely effective in the treatment of these diseases, sometimes their administration has been associated with paradoxical effects, i.e., there is an exacerbation of the inflammatory process. Tough, clinical trials of IL-17i have described cases of exacerbation or even onset of inflammatory bowel disease (IBD), such as Crohn’s disease and ulcerative colitis, after administration of these drugs in patients previously diagnosed with psoriasis (PS), psoriatic arthritis (PsA), or ankylosing spondylitis (AS). The pathophysiological mechanism of action is not well understood at present. One explanation would be that this hyperreactive inflammatory process would be triggered by Interferon 1 derived from dendritic plasma cells. Even though there are many reports in the recent literature about the role of IL17i in the onset of IBD, conclusions of studies do not converge. Some of them show an increased incidence of IBD in patients treated with IL17i, while some others affirm their safety of them. In the near future we will surely have more data emerging from ongoing meta-analyses regarding safety of use IL17i in patients who are at risk of developing IBD. Clinical and paraclinical evaluation (inflammatory intestinal markers) are carefully advised before recommending treatment with IL-17i and after initiation of treatment, and prospective surveillance by clinical and biomarkers of patients treated with IL-17i is absolutely essential to capture the onset of IBD.